Desempenho agronômico de genótipos de cártamo submetidos a compactação em latossolo de cerrado - Paludo, Juliana Terezinha Sasso (2015)
The global demand for new energy sources has boosted the cultivation of new oleaginous plants for the production of biodiesel. The crop development may be limited by soil compaction is one of the factors that influence the penetration capacity and root growth in the soil. The objective was to evaluate the agronomic performance of safflower genotype (Catthamus tintorius L.) subjected to soil density levels. The experiment was conducted in a greenhouse during the period from April to August 2015. The soil was the Oxisol collected in area under Cerrado vegetation in the layer of 0-0.20 m. The experimental design was completely randomized in four replications, with five levels of soil density (1.0, 1.2, 1.4, 1.6 and 1.8 Mg m-3 ) and ten safflower genotypes (PI 237538, PI 248385, PI 250196, PI 301049, PI 305173, PI 305205, PI 306596, PI 306603, PI 560202 and PI 613366) selected from genetic material with promising agronomic characteristics for the production of biodiesel by the Mato-grossense Institute cotton (IMAmt) in four replications. The experimental unit was represented by a pot of 9.423 dm3 , made from rigid PVC pipe of 200 mm internal diameter, 300 mm height, and it comprises three rings 100 mm, joined with tape "duct tape" the upper and lower rings pots were filled with soil density 1.0 Mg m-3 and the intermediate treatment as soil density. The experimental data were subjected to analysis of variance and the means were grouped by the Scott-Knott test at 5% probability. The statistical program used was SISVAR. Were evaluated during the experiment number of leaves, plant height, stem diameter, chlorophyll content (SPAD index) number of primary, secondary and tertiary branches, chapter number, shoot dry mass, chapters, the Total shoot, dry matter root of the upper ring, intermediate and lower dry matter total root, total dry weight, root volume of the top ring, intermediate and lower overall root volume and mass relation shoot dry / dry weight root. The increase in soil density levels showed significant changes in variables of safflower genotypes. Genotypes PI 250196, PI 301049, PI 305173 and PI 305205 showed the best agronomic performance. The PI 250196 genotype showed better root development. The dry matter production of shoots began to be influenced from the soil density 1.10 Mg m-3 , for dry root mass reduction was observed from the soil density 1.04 Mg m-3 level critical to the development of safflower genotypes was observed for values close to the ground density of 1.10 Mg m-3 .